#2 Extraction of Naturally Occuring Cannabinoids : Recent Advances - Sarker, Satyajit (Journal of Pharmaceutical Chemistry, 2022)
Cannabinoids are the compounds that bind to cannabinoid receptors (endocannabinoid system), and they are one of the most investigated groups of natural products. Cannabis sativa L. (family:Cannabaceae), an herbaceous medicinal plant from Central Asia, produces most of the ca. 150 naturally occurring cannabinoids, which are commonly known as ‘phytocannabinoids’. Among them, Δ9 tetrahydrocannabinol (Δ9-THC or simply, THC) and cannabidiol (CBD) are the two major cannabinoids. Δ9-THC mainly contributes to the psychoactive property of C. sativa, whereas CBD displays anti-psychoactive property. A few other plants are also known to produce cannabinoids, for example, Acmella oleraceae, Echinacea angustifolia, Echinacea purpurea, Helichrysum umbraculigerum andRadula marginate. There are several methods available for the extraction of natural cannabinoids from various matrices, e.g., plant materials, medicinal and cosmetic products and human biological samples. In addition to classical maceration with organic solvents, several other methods like pressurized solvent extraction, solvent heat reflux, Soxhlet extraction, supercritical fluid extraction, ultrasound-assisted extraction and microwave-assisted extraction, are now routinely used nowadays for the extraction of cannabinoids. However, the choice of any extraction method, among other things, depends on the matrix where cannabinoids need to be extracted from, and contributes to the success of subsequent analytical methods for the analysis of cannabinoids. This talk will provide a critical overview of the literature published during the last decade on the use of various extraction methods for the extraction of naturally occurring cannabinoids from various matrices.
Keywords: aaa